A Study In The Philosophy Of Surya Namaskara For The Physiological Harmonization Of The Human Body - Hemamalini, Kadek; Wirawan, Made; Oka Puspa, Anak Agung; Wibawa, Nova (Jurnal Penelitian Agama Hindu, 2024)
Surya Namaskara means worship of the Sun God. The sun as the center of the solar system is a symbol of unlimited power whose rays of universal love shine on every object and creature regardless of differences in status, ethnicity, gender, race, and class. Surya Namaskara is not just a series of physical exercises but also has depth and perfection as a spiritual practice through pranayama and asana by controlling and concentrating the fluctuations of the mind. The entire movement of Surya Namaskara represents a deep sense of appreciation for nature which manifested in various postures as a form of harmonious interaction of yogis with living creatures and the environment. This research aims to examine references to mantras/slokas in several holy books which are the philosophical basis of Surya Namaskara as well as to determine the implications of Surya Namaskara for the physiological harmonization of the human body. The method used in structuring this research is descriptive qualitative, with a phenomenological approach through data collection in the form of observation, interviews, documentation, and document study. The results of the research show that Surya Namaskara is a yadnya to the Sun God as the source of life as well as a source of energy that gives life to all creatures on Earth, and if done regularly will have implications for the system in the body, physical and mental health so that body harmonization will be realized and in ultimately it can increase intellectual and spiritual intelligence.